The Scripture and Javanese Tradition: the Meaning and Preserving of Gugur Gunung Tradition among Gunungpring’s People - Kholis, Nor; Isnaini, Subi Nur (ADDIN, 2023)
This article examines the existence of a tradition and the content of the values of the Islamic scriptures (Al-Qur’an and Hadith) inherent and practiced in the Gugur Gunung tradition carried out by the community in Gunungpring Village, Magelang. Data were collected through in-depth interviews and analyzed qualitatively through Karl Mannheim’s sociological perspective of knowledge into three meanings: objective, expressive, and documentary. The results of the study are presented as follows. The objective meaning of the Gugur Gunung tradition is a tradition that has existed for a long time and is still being maintained today in various conditions. While expressive meaning can be captured two inherent meanings, namely the meaning of life in the later days and the meaning of the inheritance of past lives from ulama. The documentary meaning of this tradition is to foster harmonization (gotong royong, tolerance, please help) and as a medium of spirituality education for the community in maintaining a tradition. Through reading the Sociology of Knowledge using the three meanings above, it can be understood that the existence of a tradition that can survive in society will always continue to be preserved if two aspects are built that are bound together. First, internally there is a spiritual belief in  the values of the past and life in the later days. Secondly, externally, it deals with the order of socio-religious harmonization in society. The various values inherent in this tradition are in line with the teachings of the Islamic scriptures. Thus these values will continue to be produced and practiced in life in society.